Surface Cracking in 05Cr17Ni4Cu4Nb Precipitation-Hardened Stainless Steel During Secondary Forging： Mechanisms and Solutions - Zhao Jiali, Xin Ruishan, Yu Zhanyang, Cao Chenxing, Xue Feng, He Yudong, Zhou Peng (Teshugang)
05Cr17Ni4Cu4Nb steel is a martensitic precipitation-hardened stainless steel that frequently exhibits surface cracking during secondary forging， significantly compromising forging efficiency and product yield.In this study， the original austenite microstructure， martensite microstructure， phase composition and hardness of the secondary forging bar surface defect samples were tested. The results demonstrate that the observed surface cracking of secondary forging bar propagates along intergranular paths， with Cu embrittlement and mixed grain structure identified as primary contributing factors. Under high-temperature forging conditions， mixed grain structure and copper segregation exhibit a synergistic interaction. Abnormal growth of some prior austenitic grains within the mixed structure reduces the total grain boundary area， leading to increased Cu atom concentration per unit boundary area. Furthermore， inhomogeneous local strain rates during forging in mixed grain structures promote stress concentration at large/small grain ， accelerating Cu segregation to grain boundaries. At forging temperatures， locally enriched Cu atoms melt at grain boundaries， forming nanoscale liquid films. This liquid acts as a "lubricant，" significantly reducing grain boundary migration resistance and promoting rapid boundary movement， thereby facilitating abnormal grain growth and mixed structure formation. Besides Cu segregation， excessively high initial forging temperature also promotes mixed grains，excessively high initial forging temperature induces an oscillating "plunge-recovery" cycle in the billet surface temperature， causing dynamic thermal inhomogeneity. Significantly enhanced grain boundary mobility in localized high-temperature micro-regions allows preferential rapid growth of certain grains， forming mixed structures. This study mitigated copper segregation by reducing the electroslag remelting rate from 7.0-6.5 kg/min to 6.0-5.5 kg/min and suppressed mixed grain tendency by lowering the initial forging temperature from 1 180 ℃ to 1 160 ℃. The optimized forging process successfully eliminated surface cracking during secondary forging.